Integrated bank analysis and valuation : a practical guide to the ROIC methodology - Chen, Sandy (Basingstoke : Palgrave Macmillan, 2014)
Provides a thorough guide to the analysis and valuation of banks. Unlike other businesses and institutions, banks have a number of unique characteristics that need to be taken into account when performing a valuation and as such traditional valuation methodologies are unsuitable and more specialized techniques required.
Includes index.
oif 22/06/15
Loan
Keywords: Banks and banking---Valuation